Solution to the flavor problem of warped extra-dimension models - Bauer, Martin; Malm, Raoul; Neubert, Matthias (Physical review letters, 2012)
A minimal solution to the flavor problem of warped extra-dimension models, i.e., the excessive mixed-chirality contribution to CP violation in K−¯¯¯¯K mixing arising from Kaluza-Klein (KK) gluon exchange, is proposed. Extending the strong-interaction gauge group in the bulk by an additional SU(3), and breaking this symmetry to QCD via boundary conditions, the constraints arising from the ϵK parameter are significantly relaxed. As a result, KK scales MKK∼2 TeV are consistent with all flavor observables without significant fine-tuning. The model predicts an extended Higgs sector featuring massive color-octet scalars and a tower of KK pseudoaxial gluon resonances, whose existence is not in conflict with recent LHC dijet bounds.